Preparation and mechanical properties influencing of Ti2AlNb powder alloy - WU Jie; WU Xiaofei; TIAN Kai; YIN Yifeng; CUI Xiaoxiao; LU Zhengguan; XU Lei (Cailiao gongcheng)
The hot isostatic pressing process is a usual powder Ti2AlNb alloy preparation method to deeply study the influence of factors such as the powder-making process on the properties of Ti2AlNb powder alloy.Ti2AlNb pre-alloyed powders are prepared by plasma rotating electrode process and electrode induction melting gas atomization， respectively， and their mixed powders are characterized. Ti2AlNb alloy is prepared using a hot isostatic pressing process.The effects of the powder-preparing process， porosity， and inclusion on the microstructure and mechanical properties of the Ti2AlNb alloy are investigated. Optimized processes are employed for the forming of various Ti2AlNb powder metallurgy components. Experimental results show that the powder-making processes affect the durability of the powder alloy， the pore defects caused by slight capsule gas leakage significantly reduce the mechanical properties of the powder Ti2AlNb alloy， and the inclusions obviously affect the consistency and stability of the room-temperature tensile properties of the powder alloy.